The Role of Green Sukuk (Islamic Bonds/ Shariah-Compliant Bonds) in Enhancing Indonesia Economic Development Strategy in The New Normal Era - Sisdianto, Ersi; ., Dakun; Robiansyah, Anton; Sharil Bin Ahmad Razimi, Moh.; Luthfiah Afifah, Aisyah (KnE Social Sciences, 2024)
This study aims to determine the significance of Green Sukuk in enhancing Indonesia’s economic development strategy in the new normal era. - The method employed was quantitative with forecasting. Furthermore, the researchers employed the least squares quantitative and historical analogy qualitative techniques. The study’s findings indicate Green Sukuk’s role in boosting Indonesia’s economic development plan in the new normal era. The implications of the study are likely to add to the body of knowledge linked to the function of Green Sukuk in enhancing Indonesia’s economic growth strategy in the new normal era. Increasing the number of issuances and contributions of State Sukuk (Islamic bonds/ shariah-compliant bonds) to APBN funding, with an annual average of roughly 30% of total Government Securities (SBN) financing. To the best of the researchers’ knowledge, this is one of the first attempts to empirically study the function of Sukuk in boosting Indonesia’s economic development strategy in the new normal era. Keywords: Green Sukuk, Development Strategy, Indonesian Economy, and the New Normal Era